2004
DOI: 10.1111/j.1440-172x.2004.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for an improved role for nurses in psychoactive substance use: Review of the literature

Abstract: Nurses form a core component of many health care systems so their role in responding to problems related to psychoactive substance use is crucial. They are often under-utilized, mainly because of anxieties concerning role adequacy, legitimacy, lack of support and failure to implement interventions in a variety of settings. Nurses have unique opportunities through interactions they have with young people, families and significant others. Training and career preparation should encompass development of innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Nurses are acknowledged as key agents in addressing substance misuse at the level of the individual, family and community (WHO/ICN, 1991, Coyne & Clancy 1996, Nkowane & Saxena 2004). Addiction nursing is involved in the assessment, management and care of individuals with problematic use of psychoactive substances (licit and illicit).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are acknowledged as key agents in addressing substance misuse at the level of the individual, family and community (WHO/ICN, 1991, Coyne & Clancy 1996, Nkowane & Saxena 2004). Addiction nursing is involved in the assessment, management and care of individuals with problematic use of psychoactive substances (licit and illicit).…”
Section: Introductionmentioning
confidence: 99%
“…‘Self‐doubt’ has been identified as a significant issue confronted by nurses caring for people who misuse substances. Some clinicians doubt their competency in the decision‐making process for this consumer group (Nkowane & Saxena 2004). To overcome this obstacle, education is required.…”
Section: Key Findingsmentioning
confidence: 99%
“…Even clinicians who have experience in caring for these consumers identified the need for more training on how to effectively work with consumers who misuse substances. To meet this need, it is suggested that training in substance use intervention be incorporated in education curricula for clinicians (Nkowane & Saxena 2004; Ryrie & McGowan 1998).…”
Section: Key Findingsmentioning
confidence: 99%
“…To provide effective care, nurses need to be equipped with appropriate knowledge and skills (Nkowane & Saxena, 2004). The published data has recommended that the trainings should focus on personal experiences and group support.…”
Section: Introductionmentioning
confidence: 96%